Estudo morfológico preliminar de materiais geopoliméricos com escória de alto forno submetidos a altas temperaturas - CORRÊA, Thiago (2021)
Portland cement, used for the production of concrete, is the principal raw material used in civil construction and this implies development, significantly in the economy of countries. However, for each ton of cement, approximately 0.95 tons of CO2 is produced, making this material prejudicial to the environment. Developed by researcher Joseph Davidovits, geopolymers are inorganic polymeric materials, with mixed microstructure (amorphous to semi-crystalline) and have basic characteristics of durability, thermal stability, in addition to being very resistant. The production is made by mixing many aluminosilicates and types of alkaline activators. The production of geopolymer mortars incorporating industrial waste has become in recent years a way to produce materials for civil construction with lower costs, but an excellent alternative for the reuse of waste economically viable. In this work the pastes and mortars were produced using Metakaolin, Blast Furnace Slag and alkaline activator. This work aims to develop geopolymeric paste and mortar and analyze their microstructures through an optical microscope when subjected to high temperatures. The results showed, through microstructural analysis, that Blast Furnace Slag and temperature can influence the material's strength.